PUBLIC HEALTH ACTIVITIES AGAINST TUBERCULOSIS IN MEXICO - MANERO FERNANDEZ, VICTOR (Universidad Minnesota, Saint Paul, EUA, 1947)
Bone marrow transfusions were found to be of value in anemia associated with fibroma of the uterus, in "sclerosis" of the uterus, in gastric ulcer, in anemia due to intestinal parasites, anemia due to chronic diarrhea, and to faulty nutrition, and anemia
AM J PUBL HEALTH
Keywords: HEALTH, ACTIVITIES, TUBERCULOSIS, MEXICO; CIENCIAS MEDICAS; SALUD PUBLICA; PREVENCION DE ENFERMEDADES